Connecting the Disconnected - Evelyn C. Casareno; Miriam C. Reniedo; Ina-mae H. Natividad; Lovely M. Dulatre; Dezy B. Damance; AaronV. Alipio (International Journal of Scientific Research and Innovative Studies, 2022)
The shift from the usual into the ‘now normal’ imposed a great challenge on the education of the young. Amidst the CoViD-19 pandemic, the delivery of instruction to the learners transitions from face-to-face to flexible learning opportunities where virtual learning platform is encouraged. This study seeks to provide hands-on experiences to the technology immigrant participants to cater the learning needs and demands of the tech-immersed learners through scaffolding. Due to the strict observance of safety protocols, the project purposively identifies only seven (7) participants for the Salindunong Program and were subjected into the two sessions: indulgence to learning community, and using the messenger, zoom, or google meet for virtual conferencing. Employing the Narrative Analysis of the Qualitative Research design as point of inquiry, narratives were gathered, validated, and analyzed thematically.Moreover, the study reveals the lived experiences and observations of digital immigrants prior to the conduct of training/intervention which centers on two (2) themes: Digital knowledge experience of the participants prior to the conduct of the training/intervention, and their impression on the significance of the scaffold on a child’s learning success in a technology-immersed learning environment. The series of sessions on the offerings of the Salindunong Program validated that the learning success of tech-immersed learners during home learning is influenced by the quality of scaffold provided by the immediate family/environment of the child.